BOOK REVIEW. TA’WIL PROBLEMATICS AS EASTERN HERMENEUTICS IN LITERARY APPROACH - Mohammad Rokib (Humaniora, 2015)
In the development of humanities in Indonesia, particularly literature, hermeneutics can be regarded as a relatively new approach. There are still a few literary studies involving solely this approach. Similarly, it has been difficult to find Indonesian written works, particularly books, that specifically discuss hermeneutics except those that are translation works. A book entitled Hermeneutika Sastra Barat dan Timur written by Abdul Hadi W.M. is one of the efforts to fill the gap in hermeneutic discourse in the approach of literary study in Indonesia.